The princess diaries - Houston, Whitney; Chase, Debra Martin; Iscovich, Mario; Wendkos, Gina; Marshall, Garry; Elizondo, Hector; Schwartzman, Robert; Andrews, Julie; Cabot, Meg.; Hathaway, Anne, 1982-; Matarazzo, Heather, 1982-; Moore, Mandy, 1984-; et al. (Burbank, CA : Disney DVD, 2001)
Mia is a frizzy-haired, glasses-wearing 15-year-old girl whose highest ambition is to become invisible. She is stunned and horrified when her grandmother shows up and informs her that she's the crown princess of the European principality Genovia.
At head of title: Disney's.
Based on the novel by Meg Cabot.
Special features: "A new princess" behind-the-scenes featurette ; 8 deleted scenes introduced by director Garry Marshall ; "The ultimate tea party" audio commentary with Julie Andrews and Anne Hathaway ; audio commentary with director Garry Marshall ; Myra music video "Miracles happen" ; Krystal music video "SuperGirl" ; THX-certified.
Director of photography, Karl Walter Lindenlaub ; edited by Bruce Green ; music by John Debney.
Anne Hathaway, Heather Matarazzo, Hector Elizondo, Mandy Moore, Caroline Goodall, Robert Schwartzman, Julie Andrews.
MPAA rating: G.
Keywords: Princesses -- Drama; Grandmothers -- Drama; Video recordings for hard of hearing people; Feature films; Comedy films